58 Should Single Group and Save (G&S) Sampling be Implemented in Spinal Cord Stimulation Surgery (SCSS)?. (12th October 2021) - McKenna, M; Ye, T; Nannapaneni, R; Patel, C
Abstract: Aim: SCSS is offered to patients who have persistent chronic neuropathic pain after trials of conservative management. Although severe bleeding complications are rare, it is common practice to take two G&S samples from patients pre-operatively. Unnecessary testing can induce patient anxiety and is a financial burden to the NHS. We aim to determine if a single G&S sample before SCSS would be beneficial, and to assess the association between number of risk factors for bleeding and blood loss in SCSS. Method: Retrospective analysis of 100 patients in one centre who had SCSS over a 3-year period. Bleeding risk factors, haemoglobin levels and complications were recorded for each patient. A review of current literature along with a cost analysis was subsequently performed. Results: An average drop in haemoglobin levels of 9g/L post-operatively was seen. No patients required blood transfusions. There was no statistically significant difference (P = 0.364) between number of risk factors and blood loss. Conclusions: The results obtained suggest that SCSS carries a low risk of adverse bleeding requiring blood transfusions. With the lack of guidelines for preoperative G&S samples it is difficult to make decisions on the amount of samples needed before SCSS. Single G&S sampling in patients without bleeding risk factors can reduce patient burden, save costs, and reduce environmental footprints left by laboratory tests. Those with risk factors may still benefit from two pre-operative G&S samples to ensure patient safety.